Does the Number of Dental Implants Affect Marginal Bone Loss in the Posterior Mandible? - Reza Tabrizi; Zeynab Shaban Nejhad; Anahita Fayyazi; Hamidreza Moslemi; Shervin Shafiei (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: Marginal bone loss (MBL) is an important factor in dental implant failure. The number of implants may affect MBL. Purpose: The aim of this study was to compare MBL in patients who received two or three implants for replacement of three missing teeth in the posterior mandible. Materials and Method: This prospective cohort study evaluated patients who required replacement of three missing teeth in the posterior mandible with dental implants. The patients were assigned to two groups. In the group 1, the edentulous area was restored with two implants and a pontic while three implants were placed for this purpose in the group 2. The MBL was compared between the two groups at 12 and 24 months after loading. Results: Forty-two implants were studied in group 1 and 36 implants in the group 2. The mean MBL was 0.90±0.12mm in the group 1 and 0.89±0.12mm in the group 2 at 12 months after loading. The mean MBL was 1.00±0.10mm in the group 1 and 0.98±0.10mm in the group 2 at 24 months after implant loading. The mean of MBL was not statistically different between the two groups at 12 months and 24 months (p> 0.05). Conclusion: It seems that the use of two or three implants for replacement of three missing teeth in the posterior mandible is not associated with an increase in MBL.